PENDAMPINGAN GURU SEKOLAH DASAR DALAM PENYUSUNAN INSTRUMEN PENILAIAN PENDIDIKAN PANCASILA BERBASIS SMART TECHNOLOGY PADA KKG DI SDN KECAMATAN DELI TUA - Gandamana, Apiek; Abda’u Ansya, Yusron; Lubis, Wildansyah; Winara; Pratama, Anggili (JS (JURNAL SEKOLAH), 2025)
Abstract: This community service activity aims to improve the competence of Elementary School teachers in compiling Smart Technology-based Pancasila Education assessment instruments. The main problems faced are the low quality of assessment instruments and the minimal use of technology in the learning evaluation process. This activity was carried out in the Kelompok Kerja Guru (KKG) of SDN Deli Tua District involving 30 teachers from various elementary schools in the area. The design of this activity includes four main stages, namely the preparation, implementation, monitoring and evaluation stages, and follow-up. Teachers are given an understanding of the principles of valid, reliable, and objective assessment, and are trained in the use of various technology applications such as Google Form, Quizizz, Plickers, and Anates. In addition, they also receive guidance in compiling and analyzing digital-based assessment instruments that can be applied in the classroom. The results of the activity show that the results of the activity show that teachers' understanding of the principles of technology-based assessment reaches 90%, with 85% of teachers being able to compile Smart Technology-based instruments and analyze them validly, reliably, and objectively. In addition, teacher readiness in integrating technology in evaluation reached 80%, supported by an increase in self-confidence of 85%, and the results of the instruments created met good quality standards with an achievement of 80%. In conclusion, this assistance has a positive impact on improving teacher competence in compiling and implementing Smart Technology-based assessment instruments, so that it is expected to improve the quality of assessment and the effectiveness of learning in Elementary Schools. Keyword: Assessment Instruments, Smart Technology, Pancasila Education   Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru Sekolah Dasar dalam menyusun instrumen penilaian Pendidikan Pancasila berbasis Smart Technology. Permasalahan utama yang dihadapi adalah rendahnya kualitas instrumen penilaian serta minimnya pemanfaatan teknologi dalam evaluasi pembelajaran. Kegiatan ini dilaksanakan di Kelompok Kerja Guru (KKG) SDN Kecamatan Deli Tua dengan melibatkan 30 guru dari berbagai sekolah dasar di wilayah tersebut. Rancangan kegiatan terdiri dari empat tahapan utama, yaitu persiapan, pelaksanaan, monitoring dan evaluasi, serta tindak lanjut. Guru diberikan pemahaman mengenai prinsip penilaian yang valid, reliabel, dan objektif, serta dilatih menggunakan aplikasi teknologi seperti Google Form, Quizizz, Plickers, dan Anates. Selain itu, mereka juga mendapatkan bimbingan dalam menyusun dan menganalisis instrumen penilaian berbasis digital yang dapat diterapkan di kelas.Hasil kegiatan menunjukkan bahwa pemahaman guru terhadap prinsip penilaian berbasis teknologi mencapai 90%, dengan 85% guru mampu menyusun dan menganalisis instrumen berbasis Smart Technology. Kesiapan guru dalam mengintegrasikan teknologi dalam evaluasi mencapai 80%, didukung oleh peningkatan kepercayaan diri sebesar 85%, serta kualitas instrumen yang dibuat mencapai 80%. Kesimpulannya, pendampingan ini berdampak positif dalam meningkatkan kompetensi guru dalam melaksanakan penilaian, sehingga diharapkan dapat meningkatkan kualitas asesmen dan efektivitas pembelajaran di Sekolah Dasar. Kata Kunci: Instrumen Penilaian, Smart Technology, Pendidikan Pancasila